UPAYA DINAS PENDIDIKAN KOTA DUMAI MENGOPTIMALKAN BANTUAN OPERASIONAL SEKOLAH TINGKAT SMP NEGERI DI KECAMATAN SUNGAI SEMBILAN KOTA DUMAI TAHUN 2015 - Yandy, Andri; Wicaksono, Baskoro (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
The research problems are how the efforts of the Department of Education Dumai optimize School Operational Assistance junior level State in Sungai Sembilan Kota Dumai 2015 and what are the factors inhibiting the City Department of Education Dumai in optimizing the School Operational Assistance junior level State in Sungai Sembilan Kota Dumai 2015. the purpose of this study was to determine the Dumai City Department of Education effort to optimize the School Operational assistance level in Sungai SMP Negeri Sembilan Kota Dumai year 2015 and to determine the factors inhibiting Dumai City Department of Education in order to optimize the School Operational assistance level in Sungai SMP Negeri Sembilan Kota Dumai 2015.This research was conducted at the Sungai Sembilan Kota Dumai. The method used is a qualitative research, data collection techniques are interviews, observation and documentationBased on the survey results revealed that efforts to optimize Dumai City Department of Education School Operational Assistance level in Sungai SMP Negeri Sembilan Kota Dumai 2015 in the implementation of distribution, data collection, monitoring is still considered weak. The scarcity of regular meetings and pertmuan done periodically to certain officials. Factors inhibiting the City Department of Education Dumai in optimizing the School Operational Assistance junior level State in Sungai Sembilan Kota Dumai 2015 are: 1) internal factors, namely, the school does not have specialized personnel in the field of administration to menangai BOS program, disbursements Bos seem complicated, because many the administration must be completed, 2) external factors, namely, the network is often busy and cause the server to die, difficult for schools to raise money for community participation.Keywords: Dumai City Department of Education, the School Operational Assistance